Perception of visitors regarding the wildlife inhabiting an archaeological site. Issue 4 (4th July 2019) - Iosif, Ruben; Vlad, Sabina E.; Stănescu, Florina; Cogălniceanu, Dan
ABSTRACT: Cultural heritage sites are often located within biodiversity hotspots, which may induce human-wildlife conflicts despite their effectiveness in attracting tourists. Mitigating these conflicts requires targeted conservation and education measures based on a solid understanding of how visitors perceive wildlife. We assessed visitors' perception of the major wildlife groups (i.e., amphibians, reptiles, water birds) that were detectable during visiting hours, within an archaeological site overlapping with a biodiversity hotspot in southeastern Romania. We explored whether age, gender, education, nationality, and awareness (i.e., prompted by guided tours, previous visits, or protection level of the area) influenced visitors' perception towards the different wildlife groups. Visitors were disturbed or felt repulsion mostly towards the less charismatic wildlife groups: snakes, frogs, and toads; the perception was significantly explained by gender, nationality and awareness. We recommend the site to be used to promote education regarding wildlife conservation, to improve visiting experience and protect less charismatic species.